A New Structure of Dynamic Voltage Restorer Based on Asymmetrical ????-source Inverters to Compensate Voltage Disturbances in Power Distribution Networks - Mahmoud Zadehbagheri; Rahim Ildarabadi; Majid Baghaei Nejad; Tole Sutikno (Institute of Advanced Engineering and Science, 2017)
As a consequence of sensitive, diverse and complex loads in today's distribution networks, improving power quality in distribution systems has attracted great attention. Power quality issues involve voltage sags, transient interrupts and other distortions in sinusoidal waveforms. Enormous methods have been proposed for power quality modification. One of the methods by which power quality problems might be addressed is to apply power electronic devices in the form of custom power devices. One of such devices is Dynamic Voltage Restorer (DVR) which is connected in series to distribution networks. At the same time, through injection of voltage to the network it is able to control voltage amplitude and phase. It is adopted lend to compensate for voltage sags through injecting series and synchronous three phase voltage. Consisted of three single phase inverters and a DC bus, it can protect susceptible loads against various types of voltage sags as well as other disturbances in the power supply. Moreover, it is capable of generating and absorbing active and reactive power. Therefore, in this paper, different structures of DVR have been investigated and eventually proposed a new structure for DVR based on Γ-Source asymmetric inverter. With the proposed structure, severe voltage sags can be retrieved 80- 90 percent. The simulation results that obtained by using MATLAB/Simulink indicate the properly functioning of proposed structure.